Boosting Local Economy Through Strategic Tourism Development in Indonesia: Meningkatkan Perekonomian Lokal Melalui Pengembangan Pariwisata Strategis di Indonesia - Vitra Pratama Ramadani; Hendra Sukmana (Universitas Muhammadiyah Sidoarjo, 2024)
This research aims to analyze and describe the strategies implemented by BUMDES Sumber Lestari in developing the Sumber Dhuwur tourist attraction. Tourism development significantly influences regional and citizen income, job creation, and economic activities. Utilizing qualitative methods, data were collected through interviews with village officials, the BUMDES chairman, local residents, and visitors, along with observations and documentation. The study uses qualitative descriptive analysis, involving data reduction, presentation, and conclusion drawing. Results indicate that BUMDES Sumber Lestari has effectively focused on infrastructure and facility development, but has yet to optimize human resource management in tourism and the creative economy. The research provides insights into strategic planning for rural tourism development, emphasizing the need for comprehensive human resource strategies to enhance competitiveness and economic impact. Highlight: Effective infrastructure and facility development by BUMDES Sumber Lestari. Human resource management needs optimization in tourism. Strategies enhance income and job creation. Keywoard: Tourism Development, BUMDES Strategy, Infrastructure, Human Resources, Economic Impact